Structures that should be Described in Higher-Symmetry, Centrosymmetric Space Groups. Part 2. - Ng, Seik Weng (Fujian Institute of Research of the Structure of Matter, 2000)
The space groups of the transition metal-Schiff base complexes, [ Ni (C5H4NO-2-CH = N-CH2CH2-N = CH-2-C5H4NO) · 2H2O] (ClO4)2 (described in Cc), [Ni(C5H4NO-Z-CH = N-CH(CH3)CH2-N = CH-2-C5H4NO) · 2H2O](ClO4)2 (described in An) and {Cu[(C5H4NO-2-CH = N-N = C(NH2)S] (H2O)}2 (NO3)2 · H2O (described in Cc), have been revised to C2/c. The general descriptions of the first two structures are unchanged in the higher-symmetry setting; for the last structure, the copper atom is re-assigned an octahedral coordination geometry instead of the reported square-pyramidal coordination geometry. The space group of {[CuO2CCH2NHCH2CO2] · (C10H8N2)}2 · 12H2O is similarly revised from P1 to P1. Atomic coordinates for the revised structures are reported.